Maximum Tolerated Volume in Nutrient Drinking Test for Diagnosis of Functional Dyspepsia - Suharjo Broto Cahyono; Neneng Ratnasari; Putut Bayupurnama; Siti Nurdjanah (Acta Interna The Journal of Internal Medicine, 2015)
Background. Methods to evaluate pathophysiology of functional dyspepsia (FD) such as barostat are invasive, expensive and not readily available. Nutrient drink test was developed as noninvasive, safe and low cost means to assess impaired gastric accommodation in FD patients. The aim of this study is to evaluate whether this test could be used for diagnostic tool for FD patients.Method. A cross sectional study was conducted from July 2014 to December 2014, at Sardjito General Hospital, Yogyakarta, Indonesia. Twenty FD patients (according Rome III criteria with normal gastroscopy) were matched by age, gender and body mass index with 20 healthy controls. All of FD patient and healthy controls ingested nutrient drink tests (UltraMilk contain 0.6 kcal /mL). Maximum tolerated volume (MTV) of each subject was recorded. Sensitivity, specifi city, positive predictive value (PPV) and negative predictive value (NPV) were analyzed.Results. Using ≤ 950 mL of maximum tolerated volume as cut off point, sensitivity, specificity, PPV and NPV were 95%, 100%, 100% and 95%.Conclusions. A nutrient drinking test can discriminate between FD patients and healthy controls with high sensitivity and specifi city. This test could be used as objective, safe and non-invasive diagnostic tool for FD patients.